Flexible and Low-Cost Emulation of Control Behaviors for Testing and Teaching of AC Microgrid - Jiashi Wang; Tingting Liu; Ke Ma (Energies, 2023)
The fast development of distributed generations enables the microgrid a popular solution for the construction of the modern power grid, where the control behaviors of power electronics converters play a crucial role. Under this scenario, the emulation of microgrid control behaviors is becoming an emerging need for the testing and teaching of the AC microgrid. However, conventional approaches, such as the dynamic simulation test and the Power-Hardware-In-Loop, are still costly or bulky to flexibly recreate the correct characteristics of microgrid including different layers of controls and the interactions among multiple converters. The dynamic simulation test is bulky and costly to emulate various types of control behaviors since all physical components in the test system may need to be adjusted. The high cost of Power-Hardware-In-Loop is mainly caused by the high-performance real-time simulator and power amplifier. In this paper, a novel emulation system is proposed for the testing of the AC microgrid. A low-cost circuit configuration, which includes two face-to-face connected DC–AC converters and some passive loads, is introduced with the possibility of flexibly emulating most of the typical control schemes in an AC microgrid. In addition, a user interface for the real-time operation and measurement of the hardware platform is introduced on a host computer to further facilitate the testing process. Finally, various control schemes in microgrids, including the voltage control, current control, droop control, and secondary control, are validated in the experiment setup based on the proposed emulation approach.